Odpowiedzi

2009-11-29T17:04:58+01:00
3x-5=4+2x
3x-2x=4+5
x=9

-5x+10=-2x-8
-5x+2x=-8-10
-3x=-18


3(x+6)-5x=2(x+9)



27-x=35
x=8

-0,5x=12


3x-4=11
8x=18,4=6x
-5x-17=-9x+3
7x+2=5+4x+9
2(x-3)+3(4-x)=5
2(x+4)-5(x+3)=2
2009-11-29T17:10:31+01:00
X=9
x=-6
x=0
x=8
x=-24
x=5
x=tu jest cos nie tak
x=5
x=4
x=11
x=-3
2009-11-29T17:13:37+01:00
3x-5=4+2x
3x - 2x = 4 +5
x = 9

-5x+10=-2x-8
-5x + 2x = -8 - 10
-3x = -18 /:(-3)
x = 6

3(x+6)-5x=2(x+9)
3x+18-5x=2x+18
-2x-2x=18-18
-4x=0
x=0

27-x=35
-x=35-27
-x=8
x=-8

-0,5x=12 /×(-2)
x=-24

3x-4=11
3x=11+4
3x=15 /:3
x=5

-5x-17=-9x+3
-5x+9x=3+17
4x=20 /:4
x=5

7x+2=5+4x+9
7x-4x=14-2
3x=12 /:3
x=4

2(x-3)+3(4-x)=5
2x-6+12-3x=5
-x=-1 /×(-1)
x=1

2(x+4)-5(x+3)=2
2x+8-5x-15=2
-3x=2+7
-3x=9 /:(-3)
x=-3